Are respectful maternity care (RMC) interventions effective in reducing intrapartum mistreatment against adolescents? A systematic review - Helen H. Habib; Jefferson Mwaisaka; Kwasi Torpey; Ernest Tei Maya; Augustine Ankomah (Frontiers Media S.A., 2023)
Intrapartum mistreatment of women by health professionals is a widespread global public health challenge. It leads to a decreased quality of maternity care and is evinced to precipitate detrimental maternal and neonatal outcomes, especially among adolescents. Relatedly, research indicates that Respectful Maternity Care (RMC) interventions are especially effective in mitigating intrapartum mistreatment and improving birth outcomes. However, evidence on the success of RMC, specifically for adolescents, is insufficient and unaggregated. Accordingly, this review specifically aims to synthesize existing evidence on RMC care provision to adolescent parturients. This review searched for relevant literature from published and gray sources including PubMed, ScienceDirect, Cochrane, CINAHL, PsycINFO, Scopus, as well as Population Council, WHO and White Ribbon Alliance data sources published between January 1990 and December 2021. Based on eligibility, studies were selected and quality appraised after which thematic analysis and narrative synthesis was conducted. Twenty-nine studies were included in the systematic review. Due to paucity and heterogeneity of quantitative studies, the review was limited to a thematic analysis. Adolescent and health provider perspectives alike underscored the burden and outcomes of mistreatment. Need for RMC interventions to improve quality of maternity care was recommended by majority of studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42020183440.